PENDAMPINGAN PERENCANAAN DESAIN PONDOK PESANTREN AL-HIKMAH ASYUHADA DI KABUPATEN SUKOHARJO - Fadhilla Tri Nugrahaini; Indrawati; Nurhasan; Dyah Widi Astuti; Alfia Magfirona (Universitas 'Aisyiyah Surakarta, 2026)
Islamic boarding schools (pondok pesantren) play a vital role as educational and religious institutions, requiring adequate physical facilities to support their activities. Historically, the construction of these facilities has often been carried out incrementally with assistance from various stakeholders. Therefore, developing a comprehensive building design plan is essential to ensure construction efficiency that aligns with short-, medium-, and long-term development strategies. This situation underscores the need for design planning assistance that integrates specific spatial needs with phased development planning. This community service program aims to assist the planning and design development process of the Al-Hikmah Asyuhada Islamic Boarding School in Sukoharjo Regency. The methods utilized include field surveys, literature reviews, interviews, and Focus Group Discussions (FGDs) to identify design requirements and formulate planning concepts. The result of this program is a comprehensive architectural design document encompassing spatial concepts, design development drawings, and architectural visualizations, which serves as a definitive reference for the institution's physical development. The direct impact experienced by the partner is the acquisition of an architectural design blueprint that functions as a guiding document for construction. The existence of this document effectively transforms the partner's development plan from a previously unguided approach into a structured, phased construction process that complies with spatial layout and building regulations.